LEGISLATION KEY MILESTONES OF CAPITAL MARKET UNION IN THE REPUBLIC OF CROATIA AND THE EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2019)
The paper presents an overview of the European Union legal framework related to capital markets, investment funds, credit rating agencies, securitization subjects and structures, primary and secondary markets’ actors and mechanisms, venture capital, social entrepreneurship and long-term investment funds. It also deals with short selling, benchmarks and prospectuses. The content of the paper is defined by the scope of activities of the European Securities and Markets Authority (its supervised entities and the scope of its prudential activities), the consequences of the 2008-2009 financial crisis, and the promises to reshape and develop financial markets and instruments in the European Union and Croatia. The paper intentionally excludes major players in the financial markets in Europe, such as credit institutions, pension funds, insurance undertakings, factoring and leasing companies. The above-mentioned elements are all key points of the strategic project of a Capital Market Union in the EU with the main goals of promoting non-banking financial services to entrepreneurs and SMEs, introducing and developing an alternative to banking loans and other traditional financing tools. These rules and regulations, colloquially called single rulebook, are also applied in the Republic of Croatia as a member of the European Union. Finally, an overview of the evolution of financial markets regulation and supervision infrastructure in Croatia starting since 1990 up to today is provided, including the laws transposing the abovementioned EU directives. The descriptive methodology, detailed analysis, critical resume and synthesis of all the researched elements are used to approach the different levels of rules necessary for future development of financial markets and instruments in Croatia and the EU. The hypothesis tested is whether the new regulatory framework achieves its goals of promoting non-conventional financial instruments in Europe and supporting economic growth.